Efficacy of acupuncture for melasma: A protocol of systematic review and meta-analysis. Issue 50 (17th December 2021) - Tang, Liheng; Xian, Jin; Zhang, Ye; Zhang, Changyun; Yu, Huijuan; Tan, Qiwen; Zhang, Xin
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Melasma is a common acquired hyperpigmentation of the skin. The clinical manifestations are light brown or dark brown patches symmetrically distributed on the cheeks, forehead, and mandibular with different shades and unclear borders. The treatment of melasma is extremely challenging due to its easy relapse and hard to cure. As a classical method of traditional Chinese medicine, acupuncture has been used to treat melasma in clinical practice. However, there is no systematic review and meta-analysis of acupuncture on melasma. This study aims to assess the efficacy of acupuncture for melasma. Methods: We will perform a comprehensive retrieval in the following electronic databases: PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure (CNKI), Wan Fang Database, VIP database, Chinese Biomedical Literature Service System (SinoMed), Chinese Biomedicine (CBM) database, and TCM Literature Analysis from inception to July 1, 2021, to identify any eligible study. We include all randomized controlled trials (RCTs) without any limitation of blinding or publication language, and exclude cohort studies and case reports. The meta-analyses will be conducted by using the Stata16. We will use the Cochrane risk of bias tool for randomized trials to assess the risk of bias of included studies. The X 2 and I 2 tests will be utilized to assess the statistical heterogeneity of evidence. We will conduct a meta-analysis if the studies can be combined. Otherwise, a narrative synthesis will be performed. Article screening and data extraction will be independently evaluated by 2 reviewers trained in methodology according to the established selection criteria. Any disagreements between the 2 reviewers will be resolved by reaching a consensus with the other authors (the third reviewer). Results: This study will systematically evaluate the clinical efficacy of acupuncture for melasma. Conclusion: The conclusion of this study will provide evidence to ensure the efficacy of acupuncture for melasma, so as to provide an objective and scientific basis for clinical practice. Ethics and dissemination: No ethical approval will be required because the data used are not linked to individual patient. The results of this review will be published in a peer-reviewed journal. Registration number: INPLASY2021110097.